Care in crisis—Is there a solution? Reflections on the Care Crisis Review 2018. Issue 1 (24th April 2019) - Holt, Kim; Kelly, Nancy
Abstract: In 2017, the number of applications for care orders in England and Wales was the highest ever recorded at 14, 207. This is a significant factor, contributing to the rise in the number of children who are looked after, which is at the highest level since 1985. The authors reflect on the recently published Care Crisis Review 2018, a sector‐led review, which examines the reasons for the rise in care proceedings and the number of children in care. The review sought to identify changes to policy and practice within local authorities and the family justice system, in an attempt to divert cases away from the family courts and to reduce the number of children in care, where it is safe to do so. Whilst the legislative framework is largely effective and the system generally works well, there is insufficient funding and resources to meet the needs of children and their families when they seek help, regardless of whether this is at an early stage or when they are in crisis and most in need of care and protection.